Fabrication of CoPcMWCNTs nanocomposite for supercapacitor applications - Sheriff A Balogun; Dina Thole; Daniel M Teffu; Daniel Masekela; Kwena D Modibane (Materials Research Express, 2025)
The advancement of sophisticated materials for supercapacitors is essential for improving energy storage efficiency, especially in scenarios that demand high power density and extended cycle life. In this study, we synthesized CoPcMWCNTs nanocomposite and investigated its supercapacitive properties. The nanomaterials fabrication was successfully confirmed using EDX, XRD, SEM, FTIR, and UV–visible spectroscopy techniques. Electrochemical techniques such as galvanostatic charge–discharge (GCD), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) were employed to determine the power density, specific capacitance, cycling stability, and energy density of the fabricated materials. Benefiting from the synergistic effects of CoPc and fMWCNTs, the hybrid supercapacitor exhibited a lower charge transfer resistance (R _ct ) of 0.11 kΩ, high specific capacitance of 508.67 F cm ^−2 , lower phase angle of 32°, high power density of 700 mW cm ^−2 , and high energy density of 138.48 mWh cm ^−2 . The findings emphasize the potential of CoPcMWCNTs nanocomposite for high-energy applications and long-term cycling performance, hence contributing to the advancement of next-generation supercapacitors.